A DSS for planning the agricultural production. (15th December 2011) - Bournaris, Thomas; Papathanasiou, Jason
In this paper, the agroPLAN decision support system (DSS) is presented; agroPLAN is a DSS for the planning of agricultural production in agricultural holdings or in agricultural areas. It is one of the main farm management applications of the agroGOV.gr portal. The utilisation of the agroPLAN DSS supports the farmer-manager in the difficult process of farm management and decision-making. In particular, agroPLAN simulates different scenarios and policies and proposes alternative production plans. It is based on a multicriteria mathematical programming model and can achieve the optimum agricultural production plan in a farm or in an agricultural area combining different criteria to a utility function under a set of constraints concerning different categories of land, labour, available capital, etc. The objective of this application is to help the farmer-user to gain control of the external environment with easy access to knowledge and information.